Housing and the secular decline in real interest rates - Markus Knell (Oesterreichische Nationalbank (OeNB), 2023)
In this paper, I study the role of housing for wealth accumulation and the determination of the equilibrium real interest rate within a continuous-time overlapping generations model that incorporates a realistic demographic structure and households that save for life-cycle and bequest reasons. The benchmark model contains three groups of dwellers: renters, homeowners with mortgages and outright owners. The latter group is assumed to inherit their dwellings, to use them as lifelong residences and to bequest them to their descendants. In addition there is also the group of the top 1% who are assumed to have higher incomes and stronger bequest motives. The calibrated model predicts a decline in the equilibrium real interest rate between 1980 and 2018 of almost 4 percentage points (pp), an increase in the wealth-to-income ratio of almost 250 pp and an increase in the share of housing wealth of almost 8 pp. All of these patterns are broadly in line with the empirical observations. In addition, the results of the model also align with other empirical regularities, like the mute response in the capital-to-income ratio, the trend in inheritance flows and the proliferation of mortgages. The paper closes with a discussion of why the assumptions about the behavior of outright owners are crucial for capturing these developments.
Keywords: D14; D31; G51; R21; 330; Housing; Wealth; Interest Rate; Saving